Tập hợp nội dung nhóm vấn đề đã được chất vấn tại các kỳ họp, phiên họp (nhiệm kỳ Quốc hội khóa XV) - Quốc hội (2024)
Bản tập hợp nội dung nhóm vấn đề đã được chất vấn tại các kỳ họp, phiên họp (nhiệm kỳ Quốc hội khóa XV).